1978
DOI: 10.1002/cne.901820510
|View full text |Cite
|
Sign up to set email alerts
|

The axonal arborizations of lateral geniculate neurons in the striate cortex of the cat

Abstract: Horseradish peroxidase (HRP) was injected into the optic radiations of adult cats. With placements close to the lateral geniculate nucleus (LGN), the enzyme diffused retrogradely along the axons of geniculocortical relay neurons, entered their cell bodies, and, after reaction with diaminobenzidine, produced a Golgi-like staining of entire neurons. When the injections were made close to the visual cortex, the enzyme diffused anterogradely and filled complete axonal arborizations in area 17.In the LGN, examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
3
2

Year Published

1981
1981
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(139 citation statements)
references
References 26 publications
8
126
3
2
Order By: Relevance
“…Earlier studies noted the presence of these intrageniculate collaterals (Ferster and LeVay, 1978;Friedlander et al, 1981;Stanford et al, 1983), and it was suggested that they innervated GABAergic thalamic reticular cells or interlaminar interneurons (Montero, 1989;Sanchez-Vives et al, 1996;Steriade et al, 1997). Interlaminar interneurons share many features of thalamic reticular neurons such as intrinsic membrane properties as well as sensitivity to various neuromodulators that differ significantly from analogous properties in intralaminar interneurons (Sanchez-Vives et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier studies noted the presence of these intrageniculate collaterals (Ferster and LeVay, 1978;Friedlander et al, 1981;Stanford et al, 1983), and it was suggested that they innervated GABAergic thalamic reticular cells or interlaminar interneurons (Montero, 1989;Sanchez-Vives et al, 1996;Steriade et al, 1997). Interlaminar interneurons share many features of thalamic reticular neurons such as intrinsic membrane properties as well as sensitivity to various neuromodulators that differ significantly from analogous properties in intralaminar interneurons (Sanchez-Vives et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to collaterals within the thalamic reticular nucleus, relay neurons of the lateral geniculate nucleus also give rise to local collaterals within the main geniculate laminae (Ferster and LeVay, 1978;Friedlander et al, 1981;Stanford et al, 1983). The targets of these intrageniculate collaterals are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be in part a result of the smaller magnification factor in area 18, and also a result of the difference in the lateral spread of afferents from the dorsal laminae of the geniculate. The largest axonal arborizations of geniculate afferents in layer 4 of area 17 are about 1 mm wide (Ferster & LeVay, 1978), while those in layer 4 of area 18 are over twice as large (D. Ferster, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…They include a subtype of the spiny stellate cells (Martin and Whitteridge, 1984), a subtype of the layer 6 pyramidal cells (Gilbert andWiesel, 1979, 1989;Martin and Whitteridge, 1984;McGuire et al, 1984;Hirsch et al, 1998), and the thalamic afferents (Ferster and LeVay, 1978;Bullier and Henry, 1979;Gilbert andWiesel, 1979, 1983;Freund et al, 1985;Humphrey et al, 1985). See Figure 2 for coronal views of these types [ss4(L4), p6(L4), and X/Y].…”
Section: Synaptic Laminar Patterns Of Spiny Cell Typesmentioning
confidence: 99%